Decreased Physical Activity and Sleep, Not Sport Specialization, Predict Illness in Middle School Athletes. (January 2021) - Watson, Andrew; Post, Eric; Biese, Kevin; Kliethermes, Stephanie; Brooks, M. Alison; Bell, David
Background: The relationships between sport specialization, physical activity, sleep, and illness in younger athletes are unknown. Therefore, the purpose of this study was to evaluate the independent effects of sport specialization, sleep, and physical activity on illness in middle school athletes. Hypothesis: Decreased sleep, decreased physical activity, and higher levels of sport specialization will be associated with an increased risk of illness among middle school athletes. Study Design: Prospective cohort study. Level of Evidence: Level 4. Methods: Parents of middle school–aged children reported baseline sport specialization (low, moderate, or high) as well as sleep duration, physical activity, and illnesses every week throughout the academic year. A mixed-effects logistic regression model was used to assess the association between illness and specialization while accounting for sleep and physical activity for the prior week as fixed effects and each individual as a random effect. Results: A total of 233 children (mean age, 12.1 ± 1.2 years; 61% male) participated, of whom 41%, 25%, and 34% were categorized as low, moderate, and high specialization, respectively. The proportion of individuals who experienced illness did not differ by specialization level (low, 76%; moderate, 70%; high, 59%; P = 0.064). In the multivariable model, the odds of illness compared with the low specialization group was not significantly different for moderate (odds ratio [OR], 0.93; 95% CI, 0.70-1.23; P = 0.61) or high specialization (OR, 0.76; 95% CI, 0.56-1.03; P = 0.073). A decreased risk of illness was associated with greater prior week sleep (OR, 0.79; 95% CI, 0.69-0.91; P < 0.001) and physical activity (OR, 0.94; 95% CI, 0.92-0.96; P < 0.001). Conclusion: Sport specialization is not associated with an increased risk of illness among middle school athletes, while increased sleep duration and physical activity appear to reduce the risk of illness. Clinical Relevance: Interventions to promote physical activity and improve sleep may reduce the risk of illness in early adolescent athletes.